Towards an evaluation of regional integration in Latin America in the 1990s - Devlin, Robert (IDB-INTAL Buenos AiresAR, 1998)
Seeks to review the strategic dimensions and rationale of regional integration, place potential costs and benefits in their proper perspective and outline directions for future research and economic policy.